'Meet the Vikings'—or meet halfway? The new Viking display at the National Museum of Denmark in Copenhagen. (18th February 2019) - Sindbæk, Søren M.
Abstract : How does a major European museum maintain its high profile as a cultural institution when faced with dwindling public funds? The decision of the National Museum of Denmark in Copenhagen to refurbish its Viking gallery under the direction of a celebrity designer has caused a stir far beyond Denmark. Appointed in 2017, the Museum's director, Rane Willerslev, has vowed to set this venerable institution on a more contemporary and commercially viable track. As one of his first major initiatives, he contracted the fashion designer and reality television star Jim Lyngvild to brush up the Viking Age gallery—one of the museum's most prominent international attractions, but strangely a hitherto somewhat neglected part of the display.